Aviation Hazards in the Sky over Thada as Revealed by Meso-scale Meteorological Modeling - Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
The airplane of Nepal Army in-route to Kathmandu Airport from Nepalgunj lost its communication with the air traffic control room from the sky of Thada of Arghakhachi District. The plane was found with breath taking crashing over the Bowang high mountain area of Baglung District. The weather pattern over the area has been numerically reconstructed with the application of Weather Research and Forecasting (WRF) model initialized with NCEP FNL meteorological and USGS land use and terrain elevation data to examined the effect of prevailing weather pattern. The reconstructed weather pattern show that the atmosphere over Thada and associated areas capture an adverse condition for aviation activities, as it appears highly turbulent and is intense subsidence prone. A detail long-term investigation usefully complemented with field observation may provide better understanding and for improved flight safety. Journal of Institute of Science and Technology, 2014, 19(2): 65-70